Design of an automatic system for monitoring the technical condition of fiber-optic cables - Alkina, Aliya; Mekhtiyev, Ali; Neshina, Yelena; Ujma, Adam; Mekhtiyev, Ruslan; Musagazhinov, Madiyar; Bilichenko, Yekaterina (Eastern-European Journal of Enterprise Technologies, 2026)
This study examines the process of monitoring the technical condition of fiber-optic cables based on the recording and analysis of changes in the pixel structure of the optical spot formed by cladding radiation under mechanical stress. The task addressed relates to the lack of affordable and easy-to-implement means for continuous monitoring of the integrity of fiber-optic communication lines capable of promptly detecting mechanical stress and unauthorized access attempts. This paper suggests a monitoring principle based on recording additional optical losses arising from microbending of the optical fiber, followed by image processing on a high-resolution photo matrix. It has been experimentally established that changes in the pixel structure of the optical spot formed by cladding radiation on the surface of the high-resolution photo matrix linearly correlate with the magnitude of the applied load and the level of additional losses. The results are attributed to the redistribution of optical power between the fiber core and cladding due to the photo-elastic effect. A distinctive feature of the proposed approach is its elimination of interferometric and reflectometric methods and the use of intelligent optical-digital pixel analysis, which reduces system cost, facilitates scalability, and is resistant to interference. The designed system could be used for continuous monitoring of fiber-optic communication lines, utility lines, as well as long-distance facilities under real-world conditions, with monitored sections up to 60 km long. Laboratory tests confirmed the system's sensitivity to mechanical loads of 5 N and its suitability for integration into existing telecommunications networks